2016
DOI: 10.3847/0004-637x/832/2/122
|View full text |Cite
|
Sign up to set email alerts
|

Why Are Pulsar Planets Rare?

Abstract: Pulsar timing observations have revealed planets around only a few pulsars. We suggest that the rarity of these planets is due mainly to two effects. First, we show that the most likely formation mechanism requires the destruction of a companion star. Only pulsars with a suitable companion (with an extreme mass ratio) are able to form planets. Second, while a dead zone (a region of low turbulence) in the disk is generally thought to be essential for planet formation, it is most probably rare in disks around pu… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
32
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(33 citation statements)
references
References 96 publications
1
32
0
Order By: Relevance
“…Both of these arguments implicitly assume that the host is not a neutron star, which we consider to be extremely unlikely given the complete absence of easily detectable massive companions like OGLE-2016-BLG-1190Lb at a few astronomical units around pulsars. See Figure1 of Martin et al (2016) and note that while the black points have similar masses to OGLE-2016-BLG-1190Lb, they have semimajor axes a∼R e and hence are likely to be stripped stars rather than planets and, in any case, not at a∼au.…”
Section: Degeneracy Breaking From Physical Constraintsmentioning
confidence: 99%
“…Both of these arguments implicitly assume that the host is not a neutron star, which we consider to be extremely unlikely given the complete absence of easily detectable massive companions like OGLE-2016-BLG-1190Lb at a few astronomical units around pulsars. See Figure1 of Martin et al (2016) and note that while the black points have similar masses to OGLE-2016-BLG-1190Lb, they have semimajor axes a∼R e and hence are likely to be stripped stars rather than planets and, in any case, not at a∼au.…”
Section: Degeneracy Breaking From Physical Constraintsmentioning
confidence: 99%
“…The pulsar timing technique has a high level of precision which allows for the detection of small, asteroid mass objects around millisecond pulsars (Thorsett & Phillips 1992;Bailes et al 1993;Blandford 1993;Wolszczan 1994Wolszczan , 1997. No asteroids have been confirmed by observations and even the detections of planets around pulsars are rare (Johnston et al 1996;Bell et al 1997;Manchester et al 2005;Kerr et al 2015;Martin et al 2016). Although, Shannon et al (2013) suggested that an asteroid belt, having a mass of about 0.05 M⊕, may be present around pulsar B1937+21.…”
Section: Introductionmentioning
confidence: 99%
“…PSR 1719-14 b is a companion of the millisecond pulsar PSR J1719-1438 (spin period 5.7 ms) (Bailes et al 2011;Martin et al 2016). It has a mass of 1M jup , with an orbital period of ∼ 7837 s, and an orbital radius of 6 http://phl.upr.edu/projects/habitable-exoplanets-catalog/ top10 7 http://www.exoplaneet.info/index.html ∼ 6.6 × 10 10 cm.…”
Section: Gold Sample Objectsmentioning
confidence: 99%
“…It has a mass of 1M jup , with an orbital period of ∼ 7837 s, and an orbital radius of 6 http://phl.upr.edu/projects/habitable-exoplanets-catalog/ top10 7 http://www.exoplaneet.info/index.html ∼ 6.6 × 10 10 cm. It is identified as a planet by many researchers (Bailes et al 2011;Martin et al 2016;Spiewak et al 2018). Websites listing this object in their planet catalogues are EU, ARCHIVE, EXOKyoto, PHLUPR, and GCEXO.…”
Section: Gold Sample Objectsmentioning
confidence: 99%